Management of Snakebites at a Rural South African Hospital - Gboyega A. Ogunbanjo (South African Family Practice)
Background: Snakebites remain a source of considerable morbidity and mortality in many countries, with an estimated global true incidence of envenomation exceeding five million a year, with about 100 000 of these cases developing severe sequelae. Despite the availability of polyvalent snake antivenom, inappropriate first aid, regional effects of envenomation and inappropriate use of antivenom result in significant and at times potentially avoidable morbidity and mortality, particularly in children. The study was undertaken in Lephalale (previously Ellisras) Hospital, Limpopo Province, due to the frequency of snakebites managed at the hospital.